Does the PBL-STEM model improve students' deductive, inductive, and reasoning skills in biology? - Eka Riana Widiyanti; Slamet Suyanto (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Environmental pollution is a critical issue that requires students to develop strong reasoning and problem-solving skills to understand and address its complexities. However, traditional learning models are not optimal in fostering high-level thinking skills. This study aimed to determine the effect of the PBL-STEM model on deductive, inductive, and considering abilities. The research method used was a quasi-experimental nonequivalent control group pretest-posttest design. The population of this study consisted of 232 tenth-grade students at Senior High Schools 1Pakem. The sampling technique used was cluster random sampling. The sample included class X.C (control group: discovery learning mode), X.D (experimental group: PBL-STEM), and X.E (placebo group: PBL). The data collection technique used in this study was a test consisting of essay questions. The data collection instrument used was 15 valid and reliable essay questions. The research data were analyzed using descriptive quantitative analysis and a one-way MANOVA test. The result of 0.00 < 0.05 means that the implementation of the STEM-based PBL learning model is effective in improving the deduction, induction, and consideration skills of grade X high school students on Environmental Pollution material. Thus, the PBL-STEM model can be an effective alternative to improve critical thinking skills in Biology learning.